Torsion simple modules over the quantum spatial ageing algebra. Issue 10 (3rd October 2017) - Bavula, V. V.; Lu, T.
ABSTRACT: Various classes of simple torsion modules are classified over the quantum spatial ageing algebra (this is a Noetherian algebra of Gelfand-Kirillov dimension 4). Explicit constructions of these modules are given and for each module its annihilator is found.